Vitamin K2, a Naturally Occurring Menaquinone, Exerts Therapeutic Effects on Both Hormone-Dependent and Hormone-Independent Prostate Cancer Cells. (24th August 2013) - Samykutty, Abhilash; Shetty, Aditya V.; Dakshinamoorthy, Gajalakshmi; Kalyanasundaram, Ramaswamy; Zheng, Gouxing; Chen, Aoshuang; Bosland, Maarten C.; Kajdacsy-Balla, André; Gnanasekar, Munirathinam
Abstract : In recent years, several studies have shown that vitamin k2 (VK2) has anticancer activity in a variety of cancer cells. The antitumor effects of VK2 in prostate cancer are currently not known. In the present study, we sought to characterize the anticancer potential of VK2 in both androgen-dependent and -independent prostate cancer cells. Our investigations show that VK2 is able to suppress viability of androgen-dependent and androgen-independent prostate cancer cells via caspase-3 and -8 dependent apoptosis. We also show that VK2 treatment reduces androgen receptor expression and PSA secretion in androgen-dependent prostate cancer cells. Our results also implicate VK2 as a potential anti-inflammatory agent, as several inflammatory genes are downregulated in prostate cancer cells following treatment with VK2. Additionally, AKT and NF-kB levels in prostate cancer cells are reduced significantly when treated with VK2. These findings correlated with the results of the Boyden chamber and angiogenesis assay, as VK2 treatment reduced cell migration and angiogenesis potential of prostate cancer cells. Finally, in a nude mice model, VK2 administration resulted in significant inhibition of both androgen-dependent and androgen-independent tumor growth. Overall, our results suggest that VK2 may be a potential therapeutic agent in the treatment of prostate cancer.